Examining the relationship between healthy nutrition and performance enhancing attitudes of team and individual athletes - Öztürk, D. (International Journal of Applied Exercise Physiology, 2021)
The aim of this study was to examine the relationship between healthy nutrition habits and performance enhancing attitudes of team and individual athletes. Three hundred-seventy active healthy athletes (169 female, 201 male) aged 18 and over, engaged in team and individuals sports participated in this study voluntarily. The Healthy Nutrition Attitude Scale, developed by Demir and Cicioglu (2019), was used to determine athletes' attitudes related to health nutrition. The attitude levels of the athletes regarding performance enhancement were determined with the Performance Enhancement Attitude Scale, which was developed by Petroczi and Aidman (2009), and adapted to Turkish language by Yildiz and Toros (2018). The level of positive nutrition, the level of attitude towards malnutrition, and the general attitude level towards healthy nutrition (HNA: total score) of men athletes were high statistically significantly higher than women athletes (p<0.05). The information on nutrition level, emotion for nutrition level, positive nutrition level, malnutrition level, healthy nutrition attitude level (HNA: total score), and performance enhancement attitude level were determined to be statistically significantly superior than non-national athletes (p<0.05). It was determined that athletes whose best rating was the International Championship had significantly better in positive nutrition, malnutrition, and healthy nutrition attitude level (HNA: total score) than athletes whose best rating was the Turkey Championship (p<0.05). It was observed that the sub-dimension scores of athletes' healthy nutrition attitudes had a descriptive effect on the performance enhancement attitude level (%1.9, r2= .019)), but this effect was not statistically significant (p> 0.05). There is a need for more studies and training sessions for athletes on sports nutrition and problems related to the use of performance enhancing supplements, and also it is very important that the psychological processes and emotional states of the athletes are managed well by both themselves and their trainers, especially before the competition periods.